Diversity of Moesziomyces (Ustilaginales, Ustilaginomycotina) on Echinochloa and Leersia (Poaceae) - Ying-Ming Li; Roger G. Shivas; Bao-Ju Li; Lei Cai (MycoKeys, 2019)
A combined ecological, morphological, and molecular approach was used to examine 26 herbarium specimens and eight strains of Moesziomyces. The phylogenetic analysis resolved eight well-supported clades, of which three contained type specimens of known species of Moesziomyces. One clade contained two specimens that produced a teleomorph in the flowers of Echinochloa kimberleyensis in Australia. The name Moesziomyces kimberleyensis is proposed for this smut fungus. Another clade contained specimens that produced sori in the flowers of Leersia hexandra. The name Thecaphora globuligera (now Moesziomyces globuligerus) is available for this species, which is lectotypified. The teleomorph of Moesziomyces antarcticus, previously known only from Japan, is found for the first time in China, on Echinochloa crus-galli.